Mandible microsurgical reconstruction with osteocutaneous fibular flap, with the assistance of a 3D model, in a trauma patient: case report - Aluisio Cardoso Marques; Bruno Meilman Ferreira; Cristiane Tavares Ferreira; Geraldo Andrade Capuchinho; Wagner Oseas Correa; Marcelo Martins Casagrande; Daniela Rocha Franco Drumond; Livia Guimaraes Bandoni (Revista Brasileira de Cirurgia Plástica, 2021)
This is a case report of the mandible microsurgical reconstruction with osteocutaneous fibular flap in a 16-year-old patient. A victim of an assault with a firearm projectile and blunt trauma to the face, resulting in a comminuted mandible fracture, loss of dental elements, and extensive soft tissue injuries. After treatment of the acute phase, we chose microsurgical reconstruction with a free fibula flap due to the mandibular defect's extension and the possibility of dental rehabilitation. The use of three-dimensional models of the mandible and fibula was exceptionally helpful in making the best surgical planning of the osteotomy areas, decreasing the surgery flap's ischemia time.